Trade Friction and Enterprise Cost Leadership Strategy: Empirical Evidence from China - Chen, Wei; Ma , Jingjuan (Transformations In Business & Economics, 2025)
Trade frictions occasionally occur with the rise of trade protectionism. Accordingly, effectively dealing with the impact of trade frictions in complex trade environments has aroused widespread concern in academic and practical circles. Although the choice of strategies has a bearing on the competitive advantage of enterprises, few empirical studies have been conducted on strategic choices based on a macro-trade environment. Drawing from competitive strategy theory and information asymmetry theory, using the data of Chinese listed companies from 2003 to 2021, the influence of trade frictions on the selection of enterprise cost leadership strategy was explored. Results show that under trade frictions, enterprises choose a cost leadership strategy to alleviate the negative impact of such obstacles. This finding holds even after a series of robustness and endogeneity tests. The action paths through which trade frictions affect enterprise cost leadership strategy are working capital management efficiency and inventory holding level. The influence of trade frictions on the selection of enterprise cost leadership strategy is mainly manifested in the samples with low management overconfidence. In addition, enterprises with high debt levels are more inclined to adopt a cost leadership strategy in the face of trade frictions. The conclusions reveal the action mechanism behind the selection of enterprise cost leadership strategy under the influence of trade frictions and provide empirical evidence for enterprises to cope with the uncertainty of the international trade environment, as well as practical insights for the real economy to reduce costs and achieve long-term sustainable development.
Keywords: trade friction; cost leadership strategy; working capital management; inventory holding level